إستراتيجية التقييم الشامل في تعليم التربية الإسلامية الموجّه إلى إنشاء الشخصية الكاملة - Agus Zainul Fitri (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2014)
[Teacher has a very heavy duty, but of the many duties of teachers, the assessment is the most difficult aspect. This happens not because of the weakness of teachers in evaluating learning outcomes in schools, because of the demands imposed on him, namely that learners must pass in learning, especially in the National Exam. This research is a kind of field research with qualitative approach to engineering design multisitus collecting data through interviews, participant observation and document study. The results of this study indicate that the strategy adopted in order to authentic assessment in the form private PAI holistic done through: (1) the transparency of the system in the initial assessment of learning; (2) the manufacture of diary; (3) specific code generation; (4) development of peer tutoring as an appraiser; (5) record makers